Interfaces Conference | Inclusion, Diversity, Access, and Equity in the Arts and Culture Sector (Onassis Foundation, 2020)
: Υπότιτλοι AUTHORWAVE Υπότιτλοι AUTHORWAVE Πιστεύω ότι αυτό είναι ένα εξαιρετικό πανεπίστημα. Είμαι πολύ γεμάτος που είμαι το μορτυριακό για αυτό. Θα ξεκινήσω με ένα πρωτοβουλίο για αυτό το πρόγραμμα, αλλά η Μιλένα είχε πολύ περισσότερο χρόνο και την έκανε πολύ καλά, πιο από πότε μπορούσα. Αλλά θυμάμαι ότι είμαι στη μεγαλύτερη πόλη των ΗΠΑ, ως παιδί μουσικών, οπότε πήγα μέσα στον Σοφέγιο, να πάω από κόντρες σε κόντρες, με τους εργαζόμενους στην περιοχή και το συγχωρισμένο πρόγραμμα, που κοιμόταν το σχόλιο, πότε θα γίνει τέλος. Ακόμα και ο John Cage είχε ένα μεγαλύτερο κοινό στην αρτ-γαλλαρία, από την κόντρ-αλή αυτή τη στιγμή. Και πιστεύω, ποιο οικονομικό πρόγραμμα ασφαλίζει αυτή τη στιγμή. Στην αρτ-γαλλαρία μου, έχω χρησιμοποιήσει όσο περισσότερο χρόνο, προσπαθώντας να φτιάξω νέα μουσική, για νέα κοινότητες, για να φτιάξω μουσική, κάτι που αυτοί οι κοινότητες θα ήθελαν να ακούσουν, αλλά επίσης να αντιμετωπίσουν όλα τα άλλα προβλήματα, όπως οι κοινότητες, όπως οι εκπαιδευτικοί σύστημοι και τέτοια. Έτσι, αυτό το πρόγραμμα είναι πραγματικά σημαντικό. Είναι σημαντικό, και το τελευταίο άνθρωπο που μιλήσα, το έκανε πίσω στον κεφάλι, μιλάμε για τις κοινότητες ενδιαφέροντας, και μιλάμε για την ραττική φυσική της κοινότητας. Και αυτό το πρόγραμμα, πιθανά περισσότερο από τα άλλα, τα οποία είναι σημαντικά και πραγματικά, μας οδηγεί στην ενδιαφέροντα και την δημιουργία, γι' αυτό το πρόγραμμα, από τις κοινότητες ενδιαφέροντας. Και αυτό είναι το λόγο που πιστεύω ότι αυτό πραγματικά σημαίνει. Δεν είναι το να καταφέρουν τους ανθρώπους να έρθουν σε αυτό που κάνουμε. Είναι να δημιουργήσουν σχέσεις δημιουργίας και να κάνουν συμμετοχή σε ένα πραγματικό πράγμα. Υπάρχουν ακόμα και δικαίες συμμετοχές για τις ενδιαφέροντες. Θα ήθελα να πω ότι κάποιες από αυτούς των ενδιαφέροντες και δημιουργώνταν σχετικά, τόσο σχετικά όσο πιστεύω ότι θα υπάρχουν, αναφαίνοντας π настόι. Αυτό το Urban Music Boxers and Troubadours, που ήταν μια σχέση μεταξύ του EUC στην Λευκωσία, και το κέντρο του Ιάννη Κυσενάκης, που δημιουργεί το UBI-Sketch, το οποίο πιστεύω είναι κάτω. Η ΕΒΙΣ εδώ είχε την ιδέα να την παρέχει στις δημοκρατικές κοινότητες, ανοίγοντας την ιδέα στους ανθρώπους που πάντα, πάντα, πάντα, δεν θα μπορούσαν να συμβουλεύονται με αυτό. Γιατί είναι αυτό εξαιρετικό? Γιατί δεν χρειάζεται το Solfeggio να το κάνει. Είναι αμέσως, εντυπωσιακό και ευχαριστικό. Και παίρνει σε εξαιρετικές εμπειρίες, που οι άνθρωποι δεν θα μπορούσαν να προσπαθούν. Έχουμε στο πρόγραμμα, συγκεκριμένως στις περιοχές της συμβουλευτικής κουλτούρας, και της χακκίνικης κουλτούρας, πιστεύω ότι όλοι γνωρίζουμε τι είναι αυτά τα πράγματα. Έχουμε δημοκρατικές εργασίες, με άνθρωποι από διαφορετικές εργασίες, διαφορετικές παραγωγές, με καμία εμπειρία σε αυτό, τότε τελειώνουμε με κοινωνικές μάτια, και πότε μπορούμε να το κάνουμε. Έχω δουλεύει με αυτό πριν από το πρόγραμμα, αλλά πέρασε σε δεύτερο τρόπο. Το electro-acoustic resource site είναι ένα ε-learning πλατφόρμα, συγκεκριμένως ξεκινώντας από το ξεκίνημα των δεύτερων σχολών, αλλά πραγματικά έχουμε τώρα εργασίες για πρωτοβουλευτικούς παιδιών, παρουσιάζοντας τους ανθρώπους να είναι δημοκρατικοί με κάποια ήχη. Δεν χρειάζεται τίποτα σύστημα. Το πιο δύσκολο για εμείς είναι να δώσουμε τους διευθυντές και διευθυντές να είναι γνωρισμένοι για να μπορούν να το παρουσιάσουν σε άλλους. Είμαι πολύ χαρούμενος για να πω ότι η κυπριακή κυβέρνηση έχει προτείνει αυτό για όλους τους παιδιούς που σχολούν μουσική μέχρι αυτό το πρόγραμμα. Με το ε-learning πλατφόρμα, υπάρχει ένα πρωτοβουλευτικό πλατφόρμα που μπορείς να παρουσιάσεις με ήχη, που είναι πολύ, πολύ εντοιχημένη για να μάθεις. Και, όπως μπορείς να δεις, υπάρχουν διευθυντές. Μιλάμε για ήχη. Μπορείς να δεις ποια ήχη χρησιμοποιείς. Μπορείς να μορφώσεις τις ήχες. Μπορείς να παρουσιάσεις με ήχη. Και μέσα από μήνα και ώρα οι παιδίς είναι παντρεμένοι. Και συνεχίζουν να παρουσιάσουν τους ήχες τους, ώστε να έχουν κάποιο σχέση με το τι κάνουν. But not only kids, people that are just going to a workshop to try something new, and we've done this in all sorts of countries in all sorts of ways. We've held other site-specific actions in sound installations, in pubs, in fab labs, and here in the public areas of the theater in Leicester. We held a visual music festival, and this is an audio-visual new media art where the image and the sound have correspondences. In a cinémathèque, for a cinema audience who would never see this stuff. We have a hub where we invite everybody who's doing initiatives of facilitation and participatory art to tell us about their projects so that we can network and share best practice. These are things that I think are relevant. They address most of these topics, but to be actually honest, the people around me are dealing with this topic on a day-to-day basis. I have much more profound experience than I do, and really, I have two minutes left. All I'm going to do is show you the names and hand over the word to them, and I look forward to the rest of this panel. Thank you all very much. So, good morning, everyone. My name is Anifvil Marissiou, and I'm here representing the project Four Seas, from conflict to conviviality through creativity and culture. The leading partner, as you can see, is Universidade Católica Portuguesa. It's the Catholic University of Portugal. I will go into a very, very brief presentation of the project. It's mainly, like most here, a cooperation project between higher education institutions and artistic institutions. It's eight partners in total. You can see the poster outside, and I will go into it a little further ahead. We deal mostly with cultural heritage, namely in museum and gallery spaces, visual arts, design and applied arts, literature, and film. Our fields of practice, like also I assume most of you, are capacity building and training, and audience development. We have a number of activities. They see listed there. We have a multi-chapter exhibition, which takes place in each of the eight countries involved, and in the end will be put together into one big catalogue of one exhibition. We have artistic and research residencies, workshops, mediation labs, conferences. Overall, we have 50-plus activities, and we have already also engaged in, as I will demonstrate, activities that weren't initially planned and that took place because of the former ones. Overall, this is a very, very brief summary. For this presentation, what I will actually be talking about is to give a few examples out of a multitude of examples that we could have chosen. Just four main activities that developed into other ones, as I will demonstrate, that showcase the 4Cs project as a case study in this topic of inclusion, diversity, access, and equity in the arts and culture sector. I will go already into the first example. Again, this is the very brief summary of the project, what we aim to explore. How culture and arts can constitute powerful resources to promote critical reflection regarding emerging forms of conflict, as well as to envision ways to deal with and diffuse conflictual phenomena affecting today's Europe. One example of how we have been doing this was the artistic residency we had in Lisbon with Dutch artist Emezi Tulema, where she worked during her residency period with several youth groups that did theater. In this one in particular, the translation of the name of the group is not great, but it's the best one possible. This theater group works with at-risk youth. As you can see, she decided to, during her residency, work with them. This residency work actually progressed into the works that she developed for our exhibition, which took place at the Kallous Kouvenkin Foundation, and you are now seeing a few photos. This was a collaborative work that she did with this group. It was a group that had never worked in a formal artistic space, such as the Kallous Kouvenkin Foundation. It was a group that actually those particular girls involved had never even been to the Kallous Kouvenkin Museum before, even though they lived in the outskirts of Lisbon, just a few minutes away. This was one example of how a specific community was involved in the initial work of research, and then the artist actually decided to involve them in the actual work of the exhibition. I didn't have the time to put the film here, but they were also invited to perform at the opening of her exhibition at the Kallous Kouvenkin Foundation. Why the project and why is the project relevant now? After decades of institutional efforts to foster a European identity or European identities, Europe is becoming a space of uncertainty, of unrest, and conflicts are emerging. In face of these current challenges, the challenge of us all living together, which shouldn't be a challenge, but it is, in an intercultural and transnational present, Europe cannot exist without recognizing the presence of others, and conviviality is of utmost importance in promoting understanding and interaction. And I bring you another example of how the project has been doing this, the mediation lab that we have in Tensta, which is just on the outskirts of Stockholm. It's part of an ongoing project that is the Silent University by Turkish artist Ahmet Ogut, and here they developed the Language Cafe of the Silent University, where mostly groups of refugee and asylum seekers come together in the artistic space to share not just their language skills, but also other types of skills. And so it's an inter-exchange program where different people come together to provide their skills, so they can teach language, but they can also teach whatever specific skill they have, and they exchange their skills that way, and as you saw in the photos, within the artistic space of Tensta, using many times the space and the exhibitions and the materials that they have at their disposal in the artistic space to conduct this work. And so here I brought also the WHO aspect, so we, like I said in the beginning, we are bringing theory and practice with the higher education institutions and the artistic institutions together to develop skills and good creative practices in conflict and post-conflict situations. So we have the higher education institutions and artistic institutions described there, but obviously in this specific topic the most important part of the WHO is actually the different typologies of audiences and publics that we bring together. And another example, this one in Barcelona, was a workshop that was actually the very first activity of the project, which was an oceanic feeling, where basically different types of communities, the illegal street vendors, who also have an association, the artistic community, the fishermen, the dock workers, they all were brought together by the Green Parrot group, who curated these activities, because it was a workshop that involved activities such as the fishermen conducting a tour in their boat of their daily work, with the street vendors and the artist community and whoever wanted to participate, then the artists bringing all of those other different communities into their studios, to their workspaces, to their exhibition space as well. So there was this inter-exchange as well of how one specific community, one specific seaside neighborhood actually contained all of these different skills and these different ways of life, and so they were able to, during this workshop, demonstrate these realities to one another. And here I come to the last example, which is divided in two, which is demonstrative of the how, how this has been impacting the conflict resolution in contemporary society through political sphere, through social relations and human behavior. And this was the initial point, was a workshop in Paris at the Ecole Nationale Supérieure des Arts Decoratifs, who developed this workshop already with migrants, but mostly focused on their own students. But throughout the workshop, they actually realized that bringing in expert people who happened to be migrants, who happened to be asylum seekers in Paris would help a lot in what they were actually trying to reach, which was the understanding that migration can actually be an asset, can actually be something to look at as a very positive aspect. And this is then what translated, so the mediation lab came as a result of the former workshop, where craftspeople this time were the ones, not the professors, but craftspeople were the ones involved in leading the workshops, in sharing their skills, sharing their expert with the design students of the school and also with the professors at the school. And this was a series that took place throughout a whole year, so different people came to share their skills in different specific fields. And time is up, so I will actually just go very, very briefly through the photos, just to demonstrate to you the diversity of skills and people that we had involved, namely, as you will see in the end, also involving children directly in these activities. Thank you very much. Thank you. Yes, this is me, Ben Evans, and I work for the British Council, not in Cambodia, but in London. I've got thoughts. I'm here to talk about a project called Europe Beyond Access. Europe Beyond Access, but I'm going to give a little bit of information about the project, but I'd rather talk about some of the ideas behind the project as I talk through it. Europe Beyond Access is currently the world's largest arts and disability project, and it's the largest ever investment in disabled artists by the European Commission. It's a large-scale creative Europe cooperation project with seven partners. Delighted that Anassis Stegi is one of our partners, along with Holland Dance Festival, Skånes Dance Theatre, Sweden's largest independent dance company, Oriente Occidente, Italian dance festival Pair Art from Novi Sad in Serbia, a learning disabled theatre company of 20 years maturity, and the British Council as the coordinating partner. And just some very brief notes, it's large-scale, it's 4 million euros, and I think that's important, not just because, not for its own sake, but rather to say that this is, yes it's 2 million euros invested by the European Commission, but it's also 2 million euros of serious arts organizations putting their core financial weight behind a project. It isn't outreach, it's not education, it's about professional artists and putting professional artists on stage. I think that's really important to stress. So yeah, I put here a statement, we believe that there are unique barriers which prevent disabled artists from developing their practice, presenting their work, building audiences, and developing sustainable careers. And that idea of European cultural sector which has barriers and is prejudiced against disabled artists is part of our core work. But I think it's not the most important thing that we're looking at in our program. I think the most important is this, that we believe that some of the very best, most innovative work in contemporary performance is being made by deaf and disabled artists. So I really want to focus on that idea, because I think we're all very used to the question of accessibility and rights, legal, moral, artistic rights, but actually I think there's an artistic case that needs to be made and articulated. So I'm just going to talk a little bit about this idea, the creative case for diversity. And so as I said, I think we're all very used to the moral case, the moral case being, you know, if everyone in the world has a right to access creativity and culture, then disabled people who amount to about 19-20% of certainly the European population have an equal right to culture. I think we all agree on that. And the legal case, I've done that one, the legal case obviously depends on which country you're in. In the UK, the Disability Discrimination Act in 1995 had a huge impact, and the Equalities Act in 2010. In Greece, it was very nice that two years ago there was a repeal of a law that prevented, legally prevented disabled people from attending conservatoires. And yes, I love it, raised eyebrows all around. Thanks Melina Makoury for that one. But also, you know, European legal infrastructures as well. So that's a separate question. But the creative case is something else. The creative case is what's the creative reason we should be doing this work? So disabled artists contribute to a richer and more innovative art sector. It's not my idea, but it is something that feels really important to say. And I'm just going to talk about that. So artists with unique experience and perspectives on the world make new and unique art. I think that's something hopefully we in the art sector understand and can recognize. And I'm so excited to be following Melina's speech, because the history of radical art is the history of artists on the periphery, developing outside mainstream institutions and structures and slowly forcing their way in. And we don't have time to go into that, but whatever you look at, whether it be the 20th century and looking at the Harlem Renaissance of the black population, African American population, developing jazz and brand new musical movements, Balanchine being influenced by black dancers and influencing contemporary ballet. The history of art is around people on the margins making exciting work and slowly those big organizations like the one I work for realizing that this is something they need, that they will be culturally missing out. So our work is partly to accelerate that realization amongst mainstream institutions. Explorations of difference or the other help us all understand the society in which we live. Artists who explore a different position or who come from an outside perspective often reflect our own societies in a new, unique and important way. And nothing says that stronger than the way that migrant artists in European Union are reflecting on the migrant crisis and how we as maybe I would say native Europeans have to reflect on that and what that means about our cultural fortress. So diversity becomes one of the creative opportunities of our time. So simply put, if you're serious about culture, you have to be serious about exploring some of those marginal arts activities and I would say arts and disability is one of those. So I'm just going to give a couple of, well I'm just going to talk about dance in particular because Europe Beyond Access focuses on dance. Some theater cross art form but mostly dance. And I just think it's really clear if you're a dance practitioner and really interested in bodies in space and the different ways of moving, then different bodies and different ways of moving become a core part of your work. This is Claire Cunningham, an artist who talks about herself as a quadruped. She has lived and used crutches, has lived experience of using crutches all of her life since she was about five years old and she talks about herself as a quadruped, as someone with four feet who brings a brand new dance for cabaret because of her lived experience of using that work. She is amazing so hopefully you get to see some of her work. This is Chiara Bassani, another of the lead artists on our program. Chiara talks about the fact that since she was born she has a very delicate bone condition and for all of her life she's been focusing on the floor in front of her and careful of every movement because a mistake means months in hospital. So you've got an artist who has a lived experience of training. She's trained all of her life with a movement vocabulary and a focus on the floor and those of you who come from a contemporary dance background know the relationship with the floor is vital to the work of contemporary dance. And this is just a photo from a restaging of those of you who know contemporary dance will know of Trisha Brown's work and this is a restaging of Trisha Brown's work. So Trisha Brown company worked with Candoco to explore what it would be like to have a brilliant, one of the world's leading repertory dance companies of people with disabilities, with disabled people and non-disabled people, but reinventing an existing work within the canon. So it's examples of being truly provocative in the art form, truly innovative. I'm not going to go through the, I've got lots of slides after this, but I'm not going to go through them to talk about the structure of the project. I can talk at length about that. But I just want to say two things. One is that I was so excited Milena by your statement that networks are the best tool to develop cultural policy and I'm delighted that Anastas have given myself and another author of a report a little space later on today. Because one of the things that already has come from this project, we're 18 months in, is we have launched the first EU arts and disability cluster. So representing nine Creative Europe projects, five Erasmus Plus projects and the first report with recommendations and demands from European cultural policy and also from some of the future cultural programmes. So this idea that actually we do need that voice to be heard because currently it is marginalised certainly within cultural making. And actually I think I'm going to leave it there, but I just think this idea of needing to articulate the artistic case, the creative case, feels really important. So we move this out of social policy, we move this out of equalities, as important as those are, and this becomes a cultural conversation and I think that still remains a big step to be made. I'm Esther Essem and I present the team of Musica, Impulse Centre for Music and the international project, European Creative Project Sounds Now. First a little explanation about Musica and then we immediately go on with our beautiful project. Musica is an art organisation and inspires people to take a conscious and adventurous approach to music and sound. Everyone is musical. In our workshop, training courses, residential programmes, festivals, concerts, we create context and room to play in order for participants to discover or rediscover their own musicality and strengthen their musical confidence. We try to bring participants and audience into contact with the wealth of historical or contemporary musical cultures and challenge them to make music and listen with new ears. We give professional musicians and teachers, conservatory students and self-taught musicians a breath of fresh air and an international perspective in order to help their musical practice grow. It's a lot of work. If you want to have more information, please ask me later on during lunch break, whatever. I'm very eager to hear your story. Now I would like to show you the trailer of Sounds Now. There's already a lot of information or little information in the booklet. There's in the poster presentation downstairs with the general schedule of what Sounds Now is, but I would like to give you the preview of the trailer. Even Christos, who is in the project, hasn't seen it yet. So, I must be honest, the first time I saw this, of course, in the Holberg, it was far too quick for me. It really was moving. I was like, oh gosh, what a lot of information. But we tested it with our new audience, different kind of groups, and we had two different kind of trailers. And they said, this one will get you to the right people. So it's not our choice. It's the choice of the new audience. In the field of music, the notation of curator is still quite new, at least compared to the visual art world. I spoke this morning to Constance. I think he is in the room somewhere. He is a visual art curator, and I was very interested, so we will have a talk later on more. But the function is not new. It has just had different names, artist director, dramatist, festival programmer, etc. In the recent decades, the borders between the roles of the artist and the roles of the curator in the very open-ended field of music are also increasingly blurred. Many musicians include curatorial strategies in their work. Both curatorial, compositional, and performative strategies include collaborative methods, interdisciplinarity, working with context as a compositional parameter, development of concert series, and alternative institutions. When Icelandic artists Hörður Kristbjörnsson and Daniel Atluson, along with hundreds of other travelers, had to wait a few hours in a transit area at an unspecified European airport, they saw their annoyance slip into supplement ecstasy as time passed. If you are unexpectedly trapped with a cross-section of all actors of human race, you see how everyone initially does their very best not to be present in that very temporary association of fellow sufferers. A little later, however, they start to realize that they are all in the same boat. The tongues come loose, and they begin to introduce themselves to each other, and faster than the water is boiling, interest in each other's background, expertise, passions, and visions of life arises. A few rounds of participatory observations brought them, both architects, the insight that people mainly live in own egocelos, celos we heard yesterday as well, and often do not even seem to realize it. Well, this realization, this awareness of living in egocelos was present within the partners of Sounds Now. Creators of new music scene are Predometry White and Muskelyn. This led to many meetings of these nine organizations you saw in the little trailer, and at the end, an application for a new project within Creative Europe program. In the end of June 2019, we got a wonderful message that Sounds Now has selected, and just a few months ago, on the 15th of December, we officially began. The aim and objectives of Sounds Now is to bring greater diversity into contemporary music by addressing music curation at all levels. It's a four-year program of training and mentoring, productions, experimentations, and formal research. We will explore and open up the social and artistic impact of the curator's role in contemporary music. This is very, very ambitious, I know, and by saying we will, we really want to try and give it a shot. But it's not going to be easy. There are going to be many new methodologies. Maybe we don't have to describe it all, because it has to develop organically, and that's what something we do in our activities. We have the curatorial lab, curators in residence with curators with experience. They come together with the curatorial lab hosted by Sounds Now partner, and the new curators in residence are able to curate a little part of the festival existing. There's a diversity program in Finland. It's going to be the first one. It's a course, so the deadline is 15th of March. If you still have people who would like to attend, please do so. It's the first week of July, and in this week there's music curating with a perspective of music curators selected by an open call. Mentors and other experts, including Sounds Now partners, are invited to teach. The course addresses conceptual notions of curating, exploring questions such as how to reach an audience, whom do curators serve exactly, what does curating mean in our time. In this way, emerging curators are offered a space to reflect, exchange on their role in art and society with experienced professionals. There will be an annual symposium. This year it will be between the 25th and 27th of September of 2020 in Berlin. All invited. You have to be very quick because at the same time there's the marathon and there's another very big spectacle, so hotels are almost booked, so please be there. It's an annual meeting, this time organized by Ultima, together with Julia Gerlach from Akademie der Kunst in Berlin. It's normally held in a different country, organized by different partners, and there we invite music professionals, composers, curators, researchers, artists and other professionals to reflect on curatorial practice in contemporary music. Okay. We have, just because we just started, we have two projects already done. One was a project with Songs of Rebellion two weeks ago, who has the premiere here. You can see on the Facebook a wonderful trailer. Thank you for this, Christos. And this week in Belgium, in Bruges Concertgebouw, there was the premiere of Musi Matrix, where we had 1400 children from the age of six, between six and seven years old, coming in class, listening to contemporary music, playing contemporary music, experimenting how to be a performer. So, I want to thank you very much for your attention. My time is up here in this moment, but I will be here during the whole day. Please come and talk to me. I'm very interested in your story. Thank you. Hello, good morning. Yeah, my story starts, in fact, in the 90s, where I had a very interesting experience sitting very often in concert halls between a few people for a far too big concert hall. Most of them were dressed in black, looked very serious, and they were listening to contemporary music performed by other people also dressed in black. And I found these kind of events quite super interesting, but also a little bit too much exclusive. I was mainly working in the field of children's theater at the time and doing music projects also for young audiences. So, my aim was to make these projects a bit less exclusive and try to include other target groups, and I started to develop projects which connect young audiences to this kind of music, which I thought was rather playful, very often creative, beautiful, and had a rather high artistic value. The key concept from where I started to develop this project was the concept of involvement. Not enough time to talk more about this. Right now, I'm the artistic director of Zonzo Compagnie besides a few other activities I'm doing. The company is based in Antwerp. What we do is we create what we call adventurous music projects for young audiences, and I'm going to guide you very quickly to the kind of activities we develop. The first kind of projects are the performances we develop, mostly small-scale performances with touring performances which have a strong focus on contemporary music, on improvised music as well, on sound art, on new forms of music theater as well, and are created in co-production with strong music ensembles, strong musicians which we invite to work with us. A few examples. The first one is Listen to the Silence. It was created a while ago, but it was our first attempt to create a show based on the artistic universe and the life of an important composer, which the first one was John Cage. It's a bit evident, but we did it. It was an experiment where we divided the audience in two groups, and they were split up sitting in two different rooms, one in a more laboratory kind of space, the other was more like a small concert hall. The show was kind of touring for a couple of seasons. The next one we created later on was called Berberio, based on the artistic universe of Luciano Berio and his partner or wife, Katie Berberian, which was created with Revue Blanche. This was very much an experiment in shifting boundaries and perspectives like Luciano Berio very much did in his compositions. The third show I would like to mention is a show based on Miles Davis, where we experimented a lot with interactive forms to let the audience decide what was going on on stage. These three types of shows we created in the past ten years, I must say, there were many others. The next type of project is what we call the Music Labyrinth. It's a collection of sound installations created by sound artists which we bring together in a labyrinth. It's a building, sometimes it's an old castle or a theater or another space where we guide the audience through the world of sound art. Our biggest brand is probably the Big Bang Festival, which was founded in 1995 already, which from then was called the Adventurous Music Festival for Young Audiences. Young Audiences are for me not only children, they are also adults. I think about 50% of our audience are adults and the other 50% are children. When we organized the festival for the first time in Lisbon at the Centre Cultural de Belem, there was a press article which said that the Big Bang Festival was taking children serious and make adults more playful. I found it a very flattering comment. So what we do is to try to avoid to go with a very educational and top-down approach. There is a very strong attempt to create equality between the people on stage and the people in the hall. We also invite musicians which are normally playing for adults and also present music which I discovered in the 90s in these rather empty concert halls. The festival is not genre-specific. We try to present all kinds of music styles and what is important is that we try to maximize the involvement of the audience with several strategies and models we developed over the years. What is also important from the beginning is that we try to invest in the artistic forms to let music interact with our audience. There is a strong focus on participation and interactivity, a lot of very specific setups we developed from the music we would like to communicate. The project got a boost also thanks to the support from Creative Europe. We are now active in 15 cities, reaching about 60,000 people every year. The partners we have in Europe are based in Antwerp, Athens, this beautiful house as well. Mr. Bozar just came in, also his house opens, there are doors for the festival. Dublin, Enschede, Ghent, Lille, Lisbon, Reykjavik will be a new partner from May onwards. There is Rennes, Rouen, Sevilla and Tallinn. Strategies for inclusion. From the 90s, where the focus was very much on involvement, we more strongly feel the need to focus on inclusion. We developed a few projects to stimulate these possibilities for inclusion. One of these projects is what we call the Nomad Project. It's a very simple concept. We invite a musician from another country and he comes locally to create a performance which we present on stage at the festival with children. This is very essential and these children are most of the time chosen out of groups or schools which normally don't have much access to our cultural houses. This is a very simple project but has a huge impact on the artistic quality, as has been said before, but it's also kind of a huge boost for the self-esteem of the participants. I'm not going to go deeper into very specific projects. There were two I wanted to mention. One was Melike Taranek, a Turkish singer who worked together with a guy working in Ghent, opening his garage in a multicultural neighborhood, just inviting the people from the neighborhood to create music projects for him. This collaboration of this Turkish singer with these people gathering together in this neighborhood, in the garage of this musician, delivered already very beautiful projects. The project before was in Beaux-Arts. Paul Griffiths is another example of this kind of strategies and 43 seconds with the last project. Ambassadors, we started a couple of years ago to work together with children who are part of the organization. They are creating footage which we use to promote the festival. They make interviews with the artists. They are functioning as a feedback group for the festival. They welcome the audience so they become more and more the face of our event. The challenge which we have now, I think it's very much expressed by this quote by Pablo Picasso, my time is up. Thank you. Hello everybody. For those of you that have been more thoroughly through the conferences program, you will see that I'm not Miss Cosetta Nicolini. Yes, I never was. Past lives, I don't know. I'm here on behalf of Cosetta and the project Atlas of Transitions because she couldn't make it. She couldn't come due to these latest restrictions of people moving from countries that are high risk due to the coronavirus. Actually, our project has this very goal. Actually, we are fighting coronavirus. Yes, not literally. I mean, not health wise, but social wise. Because I think that most of you have already noticed that one of the effects of the virus is that it has started dividing people, is creating great isolation and is changing the aspect of how we view our fellow humans. This is why I say that this is exactly the main goal of our project. It's to bring people together in a few words, actually. I don't know where to look here. As the title says, we are exploring new geographies for cross-cultural Europe. It's a large-scale cooperation creative Europe project. This is all the partners, a project from seven countries. The main goal, let's say the main axis of the project is how to use artistic practices to foster inclusion and to tackle social issues such as migration. Keywords, keywords, keywords. The second parallel axis is to promote close collaboration between the academic partners and the artistic partners. As the backgrounds of each partner are quite different and diverse, so were all the artistic results, let's say, and the approaches and the collaborations between the academics and the artists as well in its country. Here is a small graphic to see the spread of the virus in the partnering organizations. Mainly, the actions consist of workshops and mainly we try in its city to bring people together from different communities, different ethnic groups, different levels of migration, second generation, third generation, newcomers, internal migrants. Using artistic tools and in most of the cases the public space of the city. Then we have artistic productions, performance video works installation, documentary theater. It's a very large, large variety of creations that have already seen the light within the frame of the project. And we have international festivals in almost each of the partnering countries and we also have white screens. We like for you to imagine things. I will invite you to visit our web platform, it's atranstradition.eu. You will find a ton of massive information on the web platform. And we will be concluding the project with a summer school that will take place in Bologna in the 9th to 14th of June in 2020, this summer. We have the last part as I told you, we have the international university network. There's a lot of academic partners from each country collaborating, researching, being part actually of the creative processes in some cases. For instance in our case we are collaborating with the school of architecture since our organization works mostly in public space. And we have invited actually the architects to be part of the creative process by using their tools which was completely new for them. In some other cases, in other countries we have sociologists. In some cases they were dealing with the project in a more conservative way like researching or analyzing data. But in other cases they were also invited to be part of the creative process and give direct feedback to the artists and have this very vital exchange, let's say, in real time which is not always the case of academics, the artists either. And this is the end of the slideshow. You can click to exit. I will play a short video for you and then I will mute it so we can continue actually like have one or two minutes of chat. And here it is. And so this project is called Almost 10 Steps. And it's a project, a choreographic project in public space directed by Taufik Ezediu who is from Marrakesh. And it took place in Bologna in the first international festival of Atlas of Transition. And it was a joint choreography. There was an open call for citizens to attend and to participate in this action. And it was like a sort march in the city. They had to perform 100 steps from a given point to another in the very center of the city. So because the first Atlas of Transition Biennale in Bologna was mostly focused in the public space, in invading the city and trying to explore the presence of arts and people within the city center. As of the second one, and now if you won't mind, I will just pass to the second one. It's 1 minute 40 and there is no cursor, cursor is here. And as a second example, a second project that took place in the second festival in Bologna was curated by Tania Bruguera and it was entitled School of Integration. So it was another approach. There was a venue, a dance lab that was part of the university, so we used the venue to create a series of lessons and through its lesson a different ethnic community of Bologna would come and introduce themselves. And for instance we have West Africa and it was made in a very direct and humane way. People were talking about the main things that connect us all like our clothes, our food, our music, our cultures. But contrary to other initiatives it was actually making people actively participate. It was entirely up to each group to prepare and to organize themselves, to motivate their own communities and to engage them and then the time is up. Thank you very much.